Efficiency and coherent development as the main concepts of health care managers' readiness in passive defense; Experiences of Iranians healthcare managers - Fereydoon Khayeri; Seyed Jamalodin Tabibi; Leila Riahi; Kamran Hajinabi (Journal of Education and Health Promotion, 2024)
BACKGROUND: This study examines the elements of efficiency and coherent development in passive defense among healthcare managers for disaster management in Iran. MATERIALS AND METHODS: The study employs a qualitative method using conventional content analysis from 2021 to 2023. A purposive sample of 25 healthcare managers with experience in passive defense is selected. Data are collected through unstructured interviews and analyzed using conventional content analysis. RESULT: The participants’ experiences regarding the coherent efficiency development of passive defense are categorized into three main themes, namely, enhancing emergency knowledge empathic and responsible cohesion, management development planning and resources, and individual updating and flexibility. CONCLUSION: The role of passive defense is very decisive in crisis management through the strategy of efficiency and coherent development. This strategy is implemented using the concepts of enhancing disaster knowledge, empathic and responsible cohesion, management development planning and resources, and individual updating and flexibility.